Coronary artery bypass using bilateral internal thoracic artery grafts in polyarteritis nodosa. Issue 8 (11th May 2021) - Shiozaki, Yuji; Morita, Kozo; Sawa, Shintaro; Saito, Satoshi; Niinami, Hiroshi
Abstract: Polyarteritis nodosa (PAN) affects small‐ and medium‐sized arteries but rarely occurs in coronary artery aneurysms and stenosis. For patients with PAN, coronary artery bypass grafting (CABG) can be challenging, especially with respect to graft selection. We performed CABG using a bilateral internal thoracic artery (ITA) graft for a 21‐year‐old patient with PAN, with successful postoperative outcomes. Arterial grafts have the risk of stenosis in PAN, but the patient's condition was controlled by steroids and immunosuppressants, and angiography showed no stenosis. We decided to use the ITA graft as a bypass conduit and found that long‐term follow‐up and continuous treatment are necessary.